Dampak Local-based Entrepreneurship terhadap Aset Penghidupan yang Berkelanjutan: Studi Kasus Wisata Lembah Mbencirang, Mojokerto - Yuni Setyaningsih; Tony Hanoraga (Jurnal Sosial Humaniora, 2022)
Tourism is one of the most effective tools for economic development.According to Haryana, 4.5% of Indonesia's total GDP was significantlycontributed to by tourism in 2018. The World Economic Forum rankedIndonesia 40th in the Travel and Tourism Competitiveness Index (TTCI)out of 140 countries in 2019. Nonetheless, this contribution decreasedsignificantly during the covid-19 pandemic outbreak in 2020. Mursalin et.al. argued that the tourism industry was hardest hit by the pandemic'simpact on economic growth. Understanding this phenomenon, it becameintriguing to investigate the gradual tourism revival and livelihood assetsof local tourism-based enterprise in Wisata Lembah Mbencirang by theVillage Owned Enterprises (BUMDES). This study's objectives includedidentifying and analyzing the core problematization and livelihood assetsof locally based entrepreneurship, as well as its community impact. Thisstudy was conducted in Kebontunggul Village, Mojokerto, East Java. Thisstudy employed a variety of methods. Several analytical tools, includingpentagon assets and sustainable livelihood assets, were utilized. Theresults demonstrated that local entrepreneurship had both positive andnegative effects on communities. The vulnerability context that shookpeople's livelihoods must be overcome by bolstering social and humancapitals to maintain resilience, as well as the government's commitmentto enhancing policies pertaining to locally-based entrepreneurship. Inconceiving and ensuring sustainability, the community implemented avariety of livelihood strategies through adaptation. When feasible,livelihood adaptation would continue, and incomes would increase.